Dapagliflozin protects the kidney in a non-diabetic model of cardiorenal syndrome. (February 2023) - Urbanek, Konrad; Cappetta, Donato; Bellocchio, Gabriella; Coppola, Maria Antonietta; Imbrici, Paola; Telesca, Marialucia; Donniacuo, Maria; Riemma, Maria Antonietta; Mele, Elena; Cianflone, Eleonora; Naviglio, Silvio; Conte, Elena; et al.
Abstract: Cardiorenal syndrome encompasses a spectrum of disorders involving heart and kidney dysfunction, and sharing common risk factors, such as hypertension and diabetes. Clinical studies have shown that patients with and without diabetes may benefit from using sodium-glucose cotransporter 2 inhibitors to reduce the risk of heart failure and ameliorate renal endpoints. Because the underlying mechanisms remain elusive, we investigated the effects of dapagliflozin on the progression of renal damage, using a model of non-diabetic cardiorenal disease. Dahl salt-sensitive rats were fed a high-salt diet for five weeks and then randomized to dapagliflozin or vehicle for the following six weeks. After treatment with dapagliflozin, renal function resulted ameliorated as shown by decrease of albuminuria and urine albumin-to-creatinine ratio . Functional benefit was accompanied by a decreased accumulation of extracellular matrix and a reduced number of sclerotic glomeruli. Dapagliflozin significantly reduced expression of inflammatory and endothelial activation markers such as NF-κB and e-selectin. Upregulation of pro-oxidant-releasing NADPH oxidases 2 and 4 as well as downregulation of antioxidant enzymes were also counteracted by drug treatment. Our findings also evidenced the modulation of both classic and non-classic renin-angiotensin-aldosterone system (RAAS), and effects of dapagliflozin on gene expression of ion channels/transporters involved in renal homeostasis. Thus, in a non-diabetic model of cardiorenal syndrome, dapagliflozin provides renal protection by modulating inflammatory response, endothelial activation, fibrosis, oxidative stress, local RAAS and ion channels. Graphical Abstract: ga1